SPE Annual Technical Conference and Exhibition 2000
DOI: 10.2118/63227-ms
|View full text |Cite
|
Sign up to set email alerts
|

Viscous-Elastic Polymer Can Increase Microscale Displacement Efficiency in Cores

Abstract: When flooding with viscous Polymers, due to the increase in viscosity and decrease in permeability (for polymers that absorb on the rock surface), the mobility ratio compared to water flooding becomes more favorable. Therefore the volumetric sweep efficiency increases and the recovery of the reservoir on a macro scale increases also. Most people think that polymer flooding does not increase the recovery at a micro scale. But numerous results in this work do not support this conclusion. From c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(74 citation statements)
references
References 0 publications
1
70
0
3
Order By: Relevance
“…As in Figure 4A, the water-bearing PVP solution achieved a higher saturation than SDS or water alone, and invasion by both surfactant solutions occurred faster than for water alone at this porosity. Waterbearing PVP solution achieved a higher saturation because polymer flooding can change surface wettability to be more water-wet, which will increase the oil recovery [60]. Both the PVP and SDS solutions invaded at comparable rates at the highest porosity, with SDS saturating the porous bed to a slightly greater extent than the PVP solution.…”
Section: Colloids Interfaces 2018 2 X For Peer Review 8 Of 18mentioning
confidence: 99%
“…As in Figure 4A, the water-bearing PVP solution achieved a higher saturation than SDS or water alone, and invasion by both surfactant solutions occurred faster than for water alone at this porosity. Waterbearing PVP solution achieved a higher saturation because polymer flooding can change surface wettability to be more water-wet, which will increase the oil recovery [60]. Both the PVP and SDS solutions invaded at comparable rates at the highest porosity, with SDS saturating the porous bed to a slightly greater extent than the PVP solution.…”
Section: Colloids Interfaces 2018 2 X For Peer Review 8 Of 18mentioning
confidence: 99%
“…It has been reported that a successful polymer application can achieve an incremental recovery factor of higher than 5% OOIP (original oil in place) [40,41]. Due to polymer viscoelastic properties, a larger pull force is exerted on oil droplets or oil films, which reduces residual oil saturation [42].…”
Section: Mechanisms Of Polymer Floodingmentioning
confidence: 99%
“…In the surfactant polymer flood process, the addition of water-soluble polymer can expand swept volume by increasing the water viscosity and decreasing water-oil mobility ratios [13]. However, it often has a negative effect on the interfacial tension.…”
Section: Esi-ms Spectra Of Daasmentioning
confidence: 99%